2023
DOI: 10.1038/s41598-023-32322-z
|View full text |Cite
|
Sign up to set email alerts
|

Synchronized proinsulin trafficking reveals delayed Golgi export accompanies β-cell secretory dysfunction in rodent models of hyperglycemia

Abstract: The pancreatic islet β-cell’s preference for release of newly synthesized insulin requires careful coordination of insulin exocytosis with sufficient insulin granule production to ensure that insulin stores exceed peripheral demands for glucose homeostasis. Thus, the cellular mechanisms regulating insulin granule production are critical to maintaining β-cell function. In this report, we utilized the synchronous protein trafficking system, RUSH, in primary β-cells to evaluate proinsulin transit through the secr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…A recent study characterized the disrupted protein trafficking observed in islets of diabetic LepR KO db/db mice and uncovered distended and vesiculated Golgi very similar to what we see in our KD mice. 60 Misfolded proinsulin released from the ER is put forth as cause of Golgi dilation and altered morphology. 60 Incidentally, misfolded proinsulin has been suggested to occur in early stages of T2D, 61 so it is possible that increases in misfolded proinsulin cause Golgi swelling and further impair insulin trafficking and secretion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study characterized the disrupted protein trafficking observed in islets of diabetic LepR KO db/db mice and uncovered distended and vesiculated Golgi very similar to what we see in our KD mice. 60 Misfolded proinsulin released from the ER is put forth as cause of Golgi dilation and altered morphology. 60 Incidentally, misfolded proinsulin has been suggested to occur in early stages of T2D, 61 so it is possible that increases in misfolded proinsulin cause Golgi swelling and further impair insulin trafficking and secretion.…”
Section: Discussionmentioning
confidence: 99%
“…60 Misfolded proinsulin released from the ER is put forth as cause of Golgi dilation and altered morphology. 60 Incidentally, misfolded proinsulin has been suggested to occur in early stages of T2D, 61 so it is possible that increases in misfolded proinsulin cause Golgi swelling and further impair insulin trafficking and secretion.…”
Section: Discussionmentioning
confidence: 99%